A copy number variation in PKD1L2 is associated with colorectal cancer predisposition in korean population. Issue 1 (3rd October 2016) - Park, Changho; Kim, Jong‐Il; Hong, Sung Noh; Jung, Hey Mi; Kim, Tae Jun; Lee, Seungbok; Kim, Seong Jin; Kim, Hee Cheol; Kim, Duk‐Hwan; Cho, Belong; Park, Jin‐ho; Sung, Joohon; et al.
Abstract : Recently reported genome‐wide association studies have identified more than 20 common low‐penetrance colorectal cancer (CRC) susceptibility loci. Recent studies have reported that copy number variations (CNVs) are considered important human genomic variants related to cancer, while the contribution of CNVs remains unclear. We performed array comparative genomic hybridization (aCGH) in 36 CRC patients and 47 controls. Using breakpoint PCR, we confirmed the breakpoint of the PKD1L2 deletion region. High frequency of PKD1L2 CNV was observed in CRC cases. We validated the association between PKD1L2 variation and CRC risk in 1, 874 cases and 2, 088 controls (OR = 1.44, 95% CI = 1.04–1.98, p  = 0.028). Additionally, PKD1L2 CNV is associated with increased CRC risk in patients younger than 50 years (OR = 2.14, 95% CI 1.39–3.30, p  = 5.8 × 10 −4 ). In subgroup analysis according to body mass index (BMI), we found that the CN loss of PKD1L2 with BMI above or equal to 25 exhibited a significant increase in CRC risk (OR = 2.29, 95% CI 1.29–4.05, p  = 0.005). PKD1L2 CNV with BMI above or equal to 25 and age below 50 is associated with a remarkably increased risk of colorectal cancer (OR = 5.24, 95% CI 2.36–11.64, p = 4.8 × 10 −5 ). Moreover, we found that PKD1L2 variation in obese patients (BMI ≥ 25) was associated with poor survival rate ( p  = 0.026). Our results suggest that the common PKD1L2 CNV is associated with CRC, and PKD1L2 CNV with high BMI and/or age below 50 exhibited a significant increased risk of CRC. In obese patients, PKD1L2 variation was associated with poor survival. Abstract : What's new? Recent genome‐wide association studies (GWAS) have identified a number of genetic variations that are associated with colorectal cancer (CRC), including several single nucleotide polymorphisms (SNPs). However, copy number variations (CNVs) associated with CRC risk have not been extensively analyzed. In this study, the authors found that a common CNV called PKD1L2 is strongly associated with CRC, especially in young and obese individuals. This and other CNVs may thus enhance screening protocols for CRC, especially among younger adults.